PENGARUH UKURAN PERUSAHAAN, KOMPLEKSITAS OPERASI PERUSAHAAN, REPUTASI AUDITOR, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY DI BURSA EFEK INDONESIA TAHUN 2016 S/D 2018 - I Kadek Pebri Artana; Sang Ayu Putu Arie Indraswarawati; Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of company size, complexity of company operations, auditor reputation, and financial distress on audit delay. This research was conducted at the Indonesia Stock Exchange (BEI) from 2016 to 2018. A sample of 21 companies were studied in the consumer goods industry that had been registered using a purposive sampling technique. Data collection is done by non-participant observation methods. The analysis technique used is Moderated Regression Analysis (MRA). The results of the analysis that company size has a negative effect on audit delay, the complexity of company operations has a positive effect on audit delay, auditor reputation has a negative effect on audit delay, and financial distress has a positive effect on audit delay on consumer goods industry companies listed on the Indonesia Stock Exchange.